Fuelwood studies in India: myth and reality - Pandey, D.N. (Center for International Forestry Research, 2002)
This report provides an in-depth review and critical analysis of the fuelwood, wood balance and household energy studies done in India in the last decades, and the developments in the commercial energy sector. The study synthesised the trend in the consumption of domestic energy and also the reliability level of fuelwood statistics. The consumption of fuelwood has been analysed in relation to availability of forests/trees resource, urbanisation and income level. It has been found that the fuelwood consumption and production statistics estimated by most of the studies are often not reliable. Average reliance can be placed on the consumption statistics, because most of the fuelwood studies/household energy surveys have focused on he consumption part but statistics on the supply and source aspect are extremely weak and unreliable. The review of the consumption aspect has found that traditional fuel (fuelwood, crop residue and dung cake) still dominates domestic energy use in rural India and accounts for about 90% of the total. Fuelwood alone accounts for about 60% of the total fuel in rural areas. In urban areas, the consumption pattern is changing due ti increased availability of commercial fuel (LPG, kerosene, and electricity). During 1983-1999, the consumption of traditional fuel declined from 49% to 24% and LPG connection to households increased from 10% to 44%. To make fuelwood statistics reliable, it has been suggested that key factors influencing consumption of fuelwood such as, urbanisation, nearness to accessible forest/tree resource, income level and climate should be used to stratify the population and repeated physical measurement should be done estimate per capita consumption precisely. For estimating the production of fuelwood new volume growth models of trees relating to their biomass produced during life cycle should be made. And to determine the actual source of supply of fuelwood, investigators have to observe the flow of wood households and other consumption and distribution centres for a longer period, which would also cover the seasonal variation, instead of depending upon questionaires.